Wetland water balance assessment: a case study of the Sosa wetland, Maseru, Lesotho. Issue 3 (2nd February 2023) - Mokhesuoe, Fusi; Gumindoga, Webster; Molete, Sebolelo Francina
Abstract: The Sosa wetland is a sensitive wetland, situated at the headwaters of the Jordan catchment in Maseru. Due to unregulated land use activities in the past decades (2010–2020), the Sosa wetland nearly dried up. Therefore, this study performed a wetland water balance of the Sosa wetland in Lesotho for the period of 1975–2020 using GIS and remote sensing. Landsat imageries of 1975–2020 were used for land use and land cover while the Penman -Monteith and Thornthwaite methods were used to estimate evapotranspiration. Results show that water/marsh, cultivation, settlements and bare-land increased by 2.04, 4.1, 5.82 and 28.71%, respectively, from 1975 to 2020. Forest and shrubs as well as grasslands decreased by 38.83 and 1.76%, respectively, from 1975 to 2020. Evapotranspiration estimates for the period 1984–2020 were in the range of 900 −1, 071 mm/year which is substantially greater than the annual mean rainfall of the catchment which ranges from 550 to 850 mm/year. The most sensitive wetlands are found in the middle reach of the catchment and at the headwaters occupying about 16.03% of the catchment, whereas moderately sensitive wetlands occupy 39.75%. The water balance closure as a ratio of rainfall received ranged from −3.13 to −3.5. HIGHLIGHTS: Estimation of land use and land cover changes of the Jordan catchment. Compares evapotranspiration estimates. Identification of sensitive wetland areas and their conditions. Improve water resources planning and sustainability through modeling. This research assessed the water balance of the Jordan catchment. Graphical Abstract